The Effect of Different Pair-Work Types on Students' Writing Quality - Alfino, Joni; Adnan Latief, Mohammad; Widiati, Utami; Saukah, Ali (KnE Social Sciences, 2022)
Although the use of pair work in classrooms is relatively easy to employ, the pair-work technique has been attracting the attention of many researchers because this strategy is believed to be beneficial. This paper aimed to investigate the effect of different pair-work types (homogeneous, heterogeneous and randomized pairs) on students’ writing quality. Each pair wrote a single text: an argumentative essay. The average writing scores of the individual performances of the participants from the homogeneous group (n = 18), the heterogeneous group (n = 23), and the randomized group (n = 23) were compared. The results revealed that the participants in the randomized pair had the highest score (mean = 68.87), followed by the participants in the homogeneous group (mean = 64.17), and the lowest mean score was found in the heterogeneous group participants (mean = 57.13). Keywords: effect, pair work, writing quality